Japan Trench event stratigraphy: First results from IODP giant piston coring in a deep-sea trench to advance subduction zone paleoseismology - Michael Strasser; Ken Ikehara; Charlotte Pizer; Takuya Itaki; Yasufumi Satoguchi; Arata Kioka; Cecilia McHugh; Jean-Noel Proust; Derek Sawyer; J. Everest; L. Maeda; K. Hochmuth; et al. (Marine Geology, 2024)

The increasing threat to European forests from the invasive foliar pine pathogen, Lecanosticta acicola - K. Tubby; K. Adamčikova; K. Adamson; M. Akiba; I. Barnes; P. Boroń; H. Bragança; T. Bulgakov; N. Burgdorf; P. Capretti; T. Cech; M. Cleary; et al. (Forest Ecology and Management, 2023)

Strong electronic coupling between single Ru atoms and cobalt-vanadium layered double hydroxide harness efficient water splitting - Kai Zeng; Meng Tian; Xin Chen; Jinlei Zhang; Mark H. Rummeli; Peter Strasser; Jingyu Sun; Ruizhi Yang (Chemical Engineering Journal, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Overloaded! Critical revision and a new conceptual approach for snow indicators in ski tourism - B. Abegg; S. Morin; O. C. Demiroglu; H. François; M. Rothleitner; U. Strasser (International Journal of Biometeorology, 2021)
Indicators are widely used in climate variability and climate change assessments to simplify the tracking of complex processes and phenomena in the state of the environment. Apart from the climatic criteria, the snow indicators in ski tourism have been increasingly extended with elements that relate to the technical, operational, and commercial aspects of ski tourism. These non-natural influencing factors have gained in importance in comparison with the natural environmental conditions but are more difficult to comprehend in time and space, resulting in limited explanatory power of the related indicators when applied for larger/longer scale assessments. We review the existing indicator approaches to derive quantitative measures for the snow conditions in ski areas, to formulate the criteria that the indicators should fulfill, and to provide a list of indicators with their technical specifications which can be used in snow condition assessments for ski tourism. For the use of these indicators, a three-step procedure consisting of definition, application, and interpretation is suggested. We also provide recommendations for the design of indicator-based assessments of climate change effects on ski tourism. Thereby, we highlight the importance of extensive stakeholder involvement to allow for real-world relevance of the achieved results.

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Epistemological dimensions of the water–energy–food nexus approach: reply to discussions of “Challenges in operationalizing the water–energy–food nexus” - C. Cudennec; J. Liu; J. Qi; H. Yang; C. Zheng; A. K. Gain; R. Lawford; L. de Strasser; P. T. Yillia (Hydrological Sciences Journal, 2018)

Challenges in operationalizing the water–energy–food nexus - J. Liu; H. Yang; C. Cudennec; A.K. Gain; H. Hoff; R. Lawford; J. Qi; L. de Strasser; P.T. Yillia; C. Zheng (Hydrological Sciences Journal, 2017)

Modulation of GPCRs by monovalent cations and anions - Andrea Strasser; Hans-Joachim Wittmann; Erich H. Schneider; Roland Seifert (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Pharmacological postconditioning by bolus injection of phosphodiesterase-5 inhibitors vardenafil and sildenafil - Bernd Ebner; Annette Ebner; Anna Reetz; Stefanie Böhme; Antje Schauer; Ruth H. Strasser; Christof Weinbrenner (Molecular and Cellular Biochemistry, 2013)

Uncoupled eNOS annihilates neuregulin-1β-induced cardioprotection: a novel mechanism in pharmacological postconditioning in myocardial infarction - Bernd Ebner; Stefan A. Lange; Thomas Eckert; Clementine Wischniowski; Annette Ebner; Rüdiger C. Braun-Dullaeus; Christof Weinbrenner; Carsten Wunderlich; Gregor Simonis; Ruth H. Strasser (Molecular and Cellular Biochemistry, 2013)

Inhibition of anti-apoptotic signals by Wortmannin induces apoptosis in the remote myocardium after LAD ligation: evidence for a protein kinase C-δ-dependent pathway - Stephan Wiedemann; Teresa Wessela; Kerstin Schwarz; Dirk Joachim; Marcel Jercke; Ruth H. Strasser; Bernd Ebner; Gregor Simonis (Molecular and Cellular Biochemistry, 2013)

A hypothesis of the Senoumi submarine megaslide in Suruga Bay in Japan—based on the undrained dynamic-loading ring shear tests and computer simulation - K. Sassa; B. He; T. Miyagi; M. Strasser; K. Konagai; M. Ostric; H. Setiawan; K. Takara; O. Nagai; Y. Yamashiki; S. Tutumi (Landslides, 2012)

The pro-apoptotic BH3-only protein Bid is dispensable for development of insulitis and diabetes in the non-obese diabetic mouse - Zia U. A. Mollah; Jibran Wali; Mark D. McKenzie; Balasubramanian Krishnamurthy; Kate L. Graham; Stacey Fynch; Joshua Szanyi; Pere Santamaria; Thomas Brodnicki; Janette Allison; Andreas Strasser; Thomas W. H. Kay; et al. (Apoptosis, 2011)

Increased P2X7R expression in atrial cardiomyocytes of caveolin-1 deficient mice - K. Barth; C. Pfleger; A. Linge; J. A. Sim; A. Surprenant; N. Steinbronn; R. H. Strasser; M. Kasper (Histochemistry and Cell Biology, 2010)

Ischemic post-conditioning reduces infarct size of the in vivo rat heart: role of PI3-K, mTOR, GSK-3β, and apoptosis - Claudia Wagner; Diana Tillack; Gregor Simonis; Ruth H. Strasser; Christof Weinbrenner (Molecular and Cellular Biochemistry, 2010)

Stimulation of adenosine A2b receptors blocks apoptosis in the non-infarcted myocardium even when administered after the onset of infarction - Gregor Simonis; Stephan Wiedemann; Dirk Joachim; Christof Weinbrenner; Rainer Marquetant; Ruth H. Strasser (Molecular and Cellular Biochemistry, 2009)

Limited genetic variation and structure in softshell clams (Mya arenaria) across their native and introduced range - C. A. Strasser; P. H. Barber (Conservation Genetics, 2009)

Foodborne outbreak of hepatitis A, November 2007–January 2008, Austria - D. Schmid; R. Fretz; G. Buchner; C. König; H. Perner; R. Sollak; A. Tratter; M. Hell; M. Maass; M. Strasser; F. Allerberger (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Receptor-independent sensitization of the adenylyl cylase after chronic treatment with cyclosporine A - G. Simonis; T. Christ; S. K. Bährle; M. Pena; S. P. Schoen; R. Marquetant; U. Ravens; R. H. Strasser (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Chelerythrine treatment influences the balance of pro- and anti-apoptotic signaling pathways in the remote myocardium after infarction - Gregor Simonis; Stephan Wiedemann; Kerstin Schwarz; Torsten Christ; Daniel G. Sedding; Xinjian Yu; Rainer Marquetant; Ruediger C. Braun-Dullaeus; Ursula Ravens; Ruth H. Strasser (Molecular and Cellular Biochemistry, 2008)

Protein kinase C in the human heart: differential regulation of the isoforms in aortic stenosis or dilated cardiomyopathy - Gregor Simonis; Steffen K. Briem; Steffen P. Schoen; Manja Bock; Rainer Marquetant; Ruth H. Strasser (Molecular and Cellular Biochemistry, 2007)

Dual mechanism of autoregulation of protein kinase C in myocardial ischemia - Gregor Simonis; Steffen P. Schoen; Martin U. Braun; Stefan Lichte; Rainer Marquetant; Ruth H. Strasser (Molecular and Cellular Biochemistry, 2007)

Association of OPRM1 A118G variant with the relative reinforcing value of nicotine - R. Ray; C. Jepson; F. Patterson; A. Strasser; M. Rukstalis; K. Perkins; K. G. Lynch; S. O’Malley; W. H. Berrettini; C. Lerman (Psychopharmacology, 2006)

Analysis of mechanisms contributing to AraC-mediated chemoresistance and re-establishment of drug sensitivity by the novel heterodinucleoside phosphate 5-FdUrd-araC - S. Maier; S. Strasser; P. Saiko; C. Leisser; S. Sasgary; M. Grusch; S. Madlener; Y. Bader; J. Hartmann; H. Schott; R. M. Mader; T. Szekeres; et al. (Apoptosis, 2006)

Apoptosis at a distance: Remote activation of caspase-3 occurs early after myocardial infarction - Kerstin Schwarz; Gregor Simonis; Xinjian Yu; Stephan Wiedemann; Ruth H. Strasser (Molecular and Cellular Biochemistry, 2006)

Influence of histamine release on postoperative vomiting (POV) following gynaecological laparoscopic surgery - K. Kimura; D. Rsch; C. Strasser; M. Lengkong; H. Wulf; M. Koller; I. Celik (Inflammation Research, 2004)

Regulation of protein kinase C isozymes in volume overload cardiac hypertrophy - Martin U. Braun; Paul LaRosée; Gregor Simonis; Mathias M. Borst; Ruth H. Strasser (Molecular and Cellular Biochemistry, 2004)

Metarhizium anisopliae, a potential agent for the control of grape phylloxera - M. Kirchmair; L. Huber; M. Porten; J. Rainer; H. Strasser (BioControl, 2004)

Molecular cloning of cDNA encoding N-acetylglucosaminyltransferase II from Arabidopsis thaliana - R. Strasser; H. Steinkellner; M. Borén; F. Altmann; L. Mach; J. Glössl; J. Mucha (Glycoconjugate Journal, 1999)